Urinary Incontinence Severity, Depression and Anxiety Relation in Osteoporosis Patients - Berk, Ejder; Baykara, Sema (Galenos Yayincilik, 2020)
Objective: The present study aimed to analyze the relation between urinary incontinence (UI) severity and depression, anxiety and quality of life in osteoporosis patients. Materials and Methods: Based on the bone mineral density (BMD) measurements conducted on the lumbar vertebra and femoral neck regions with dual-energy X-ray absorptiometry, those with BMD values between -1 and -2.5 standard deviation (SD) were considered as osteopenia patients (n=39), those with -2.5 SD or higher values were considered as osteoporosis patients (n=37), and those with BMD values lower than -1 SD and without any disease history were determined as the control group (n=37). Socio-demographic data form, Incontinence Severity index (ISI), Quality of Life scale (SF-36), Beck Depression inventory (BDI), and Beck Anxiety inventory (BAI) were applied to all participants. Results: It was determined that there were significant differences between the control group and the osteoporosis group, and between the osteoporosis group and the osteopenia group based on ISI scores, which was higher in the osteoporosis group. As the ISI score increased, BDI and BAI scores increased as well. There was no correlation between ISI score and quality of life subscales. Conclusion: UI is a common condition among osteoporosis patients and the severity of UI increases with a decrease in BMD. Both osteoporosis and UI could lead to high level of depression and anxiety. The investigation of the presence and severity of UI, questioning of the depression and anxiety in osteoporosis patients would contribute to the management of the disease.
Osteoporoz hastalarında İdrar İnkontinansı şiddeti, depresyon ve anksiyete İlişkisi
Keywords: Osteoporosis; incontinence severity; depression; anxiety